DENSITY VARIATION EFFECTS ON CROSS DIMENSION (CD) STRENGTH OF PHENOLIC MULTILAYERED COMPOSITES FABRICATED VIA VARTM - Nasir, M. A.; Khan, Z.; Ullah, Mudaser; Pasha, R. A.; Rahman, R. A.; Ali, Q.; Anas, S.; Nauman, S.; Amin, S. (The Nucleus, 2014)
Different phenolic composites categorized on the basis of different reinforcing fibers, each fiber has a constant length of 50 mm in its respective composite grade, are investigated on the basis of varying number of piles per square area of tested zone. As the piles differ in interested zone then resultantly density is changed for each composite grade, although the resin and hardener are k ept constant for each sample of tested composite type. Vacuum Assisted Resin Transfer Molding (VARTM) technique is used to synthesis all phenolic composites used in this research. During synthesis of each grade the same resin (Resole) and hardener (Ry lex30) are used in VARTM setup, however the fiber volume ratio is changed from 52-60% with respect to density range utilized in this work. Detail design description of VARTM is also discussed and optimized up to maximum scale to acquire compact, uniformly strengthen and porosity banned specimens. Cross Dimension (CD) Tensile and flexure strength variability with respect to density (changing fiber volume ratio) of each grade is viewed on experimental basis and tried to explain their behavior.